Opini Digital Isu Kenaikan PPN 11% - Hadi, Maulana Fadia; Suratnoaji, Catur (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The issue of the 11% VAT rate increase policy being one of the issues that is widely discussed by the general public. At the beginning of April 2022 the PPN 11% keyword appeared on the trending topic Twitter which became a medium for the public to discuss the VAT increase policy by voicing their opinions regarding this issue. This research aim to mapping the communication network on the VAT increase issue using the keywords